Comprehensive analysis of REST corepressors (RCORs) in pan-cancer - Zheng, Rong; Pan, Yingying; Liu, Xinhui; Liu, Feiye; Li, Aimin; Zheng, Dayong; Luo, Yue (Frontiers in Cell and Developmental Biology, 2023)
REST corepressors (RCORs) are the core component of the LSD1/CoREST/HDACs transcriptional repressor complex, which have been revealed differently expressed in various cancers, but the therapeutic and prognostic mechanisms in cancer are still poorly understood. In this study, we analyzed the expression, prognostic value, molecular subtypes, genetic alteration, immunotherapy response and drug sensitivity of RCORs in pan-cancer. The hepatocellular carcinoma (HCC) stemness index, micro-environment models and regulatory networks of RCORs in HCC were constructed by TCGA and GSCA database. Vitro investigations were conducted to confirm the role of RCOR1 in HCC cells. The expression of RCORs varied among different cancers, which have prognostic value in some cancers. Cancer subtypes were classified according to the expression of RCORs with clinical information. RCORs were significantly correlated to immunotherapy response, drug sensitivity and genetic alteration in pan-cancer. In HCC, RCORs were considered as potential predictor of stemness and also had association with immune infiltration. The ceRNA-TF-kinase regulatory network of RCORs was constructed. RCOR1 acts as an oncogene in HCC and promotes the proliferation of HCC cells by inhibiting cell cycle arrest and cell apoptosis. Conclusions: This study revealed the potential molecular mechanisms of RCORs pan-cancers, offering a benchmark for disease-related research.